State Trust Lands in the West, Updated Edition : Fiduciary Duty in a Changing Landscape. - Culp, Peter W.; Laurenzi, Andy.; Tuell, Cynthia C. (Cambridge, MA : Lincoln Institute of Land Policy, 2015)
This comprehensive report offers state trust land managers the latest strategies andtools for asset management, residential and commercial development, conservation use, and collaborative planning. Land managers will learn how to fulfill their trust responsibilitieswhile producing larger revenues for trust beneficiaries, accommodating publicinterests, and more.
AcknowledgementsAbout the Authors; About the Lincoln Institute of Land Policy; About the Sonoran Institute; About Western Lands and Communities; Ordering Information
Print version record.
eBooks on EBSCOhost
Keywords: Land trusts -- United States; Land trusts -- West (U.S.); Land trusts; United States; West United States